The Relationship of Work Motivation with Nurse Job Satisfaction Factors: A Systematic Review - Erlina, Yeni; Kusnanto, Kusnanto; Mishbahatul, Eka (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Nurse job satisfaction is believed to determine patient satisfaction which has a significant impact on the quality of work motivation and increases productivity. This review aimed to look at the relationship of work motivation with factors of job satisfaction in nurses. The methods involved:1) used Scopus, Sage Journals, and Science Direct databases 2) journal search starts 20-25 December 2020 3) Journal search used the English Language 4) Used keywords Work Motivation, Job Satisfaction, and Factors of Job Satisfaction in Nurses 5) Used the PICOS approach. The total journals obtained were 178 and then analyzed. Fifteen corresponding journals were appropriate. Work motivation was positively related to nurse job satisfaction. Three main themes affect the work satisfaction and dissatisfaction of nurses, there are spiritual feelings, work environment factors, and work motivation. This review concludes that work motivation was the most influential factor for increasing nurse job satisfaction supported by achievement of purpose